2017
DOI: 10.1088/1361-6528/aa8425
|View full text |Cite
|
Sign up to set email alerts
|

Very large phase shift of microwave signals in a 6 nm Hf x Zr1−x O2 ferroelectric at ±3 V

Abstract: In this letter, we report for the first time very large phase shifts of microwaves in the 1-10 GHz range, in a 1 mm long gold coplanar interdigitated structure deposited over a 6 nm Hf Zr O ferroelectric grown directly on a high resistivity silicon substrate. The phase shift is larger than 60° at 1 GHz and 13° at 10 GHz at maximum applied DC voltages of ±3 V, which can be supplied by a simple commercial battery. In this way, we demonstrate experimentally that the new ferroelectrics based on HfO could play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…However, we have demonstrated that extraordinary tunability of microwave devices can be obtained at very low DC voltages, not exceeding ± 3 V . In this respect, we have demonstrated that the phase shift of an interdigitated phase shifter in coplanar technology, fabricated at the wafer scale on HfZrO/high resistivity Si, is 60 0 at 1 GHz and 13 0 at 10 GHz, if the applied DC voltage is within the range ± 3 V. The DC voltage is so low that it can be provided by a battery . Moreover, by integrating two such phase shifters in the arm of an antenna array consisting of two patch antennas we have shown that the HfZrO phased antenna array is able to steer the radiation pattern at 2.55 GHz with 25 0 for very low bias voltages, of ±1 V .…”
Section: D Ferroelectrics and Their Applicationsmentioning
confidence: 95%
“…However, we have demonstrated that extraordinary tunability of microwave devices can be obtained at very low DC voltages, not exceeding ± 3 V . In this respect, we have demonstrated that the phase shift of an interdigitated phase shifter in coplanar technology, fabricated at the wafer scale on HfZrO/high resistivity Si, is 60 0 at 1 GHz and 13 0 at 10 GHz, if the applied DC voltage is within the range ± 3 V. The DC voltage is so low that it can be provided by a battery . Moreover, by integrating two such phase shifters in the arm of an antenna array consisting of two patch antennas we have shown that the HfZrO phased antenna array is able to steer the radiation pattern at 2.55 GHz with 25 0 for very low bias voltages, of ±1 V .…”
Section: D Ferroelectrics and Their Applicationsmentioning
confidence: 95%
“…Adapted with permission. [14] Copyright 2017, IOP Publishing Ltd. Table 1. Basic physical properties of Hf ZrO and the nanoelectronic areas where they are applied.…”
Section: Atomically Thin Ferroelectricsmentioning
confidence: 99%
“…HfO 2 doped with Zr) and some applications are already based on their properties, such as intense piezoelectric properties [4] and pyroelectric response [5]. We have recently shown theoretically that an extraordinary tunability can be obtained based on Hf x Zr 1 − x O 2 ferroelectrics [6] and we have demonstrated experimentally that phase shifters with phase shifts larger than 60° at 1 GHz and 13° at 10 GHz, at maximum applied DC voltages of ±3 V, are working with moderate losses [7]. We are continuing this research demonstrating that the phased array in Fig.…”
Section: Electromagnetic Design and Fabrication Of The Ferroelectric‐mentioning
confidence: 99%
“…We are continuing this research demonstrating that the phased array in Fig. 1 a is able to shift its main lobe with 25° for bias voltages of only ±1 V. The proposed antenna system has two interdigital phase shifters (modelling and dimensions as in [7]), one for each antenna (see Fig. 1 b , with design and fabrication details), and the two antennas are distanced at λ /2 for broadside radiation ( λ is the free‐space wavelength, whereas λ g is the guided wavelength).…”
Section: Electromagnetic Design and Fabrication Of The Ferroelectric‐mentioning
confidence: 99%